Bangladesh : Improving Competitiveness through Trade Policy Reforms - World Bank (Washington, DC, 2012)
In an increasingly competitive, globalizing world, Bangladesh needs to rationalize its tariff structure and lower overall protection so that its exports can compete in world markets. At the same time, the government needs to protect revenues in a fiscally-constrained year. This note proposes a package of tariff reforms that simplifies the rate structure, lowers average nominal protection, improves economic efficiency and is virtually revenue neutral. Adverse revenue impact, if there are any, could be addressed by strengthening the large taxpayers units, reducing the numerous exemptions in value-added tax (VAT), and expanding the tax base.